Proposed new interior design for The Cat’s Pyjamas / Aina Zailetta Abdul Rahman - Abdul Rahman, Aina Zailetta (Faculty of Architecture, Planning and Surveying, 2007)
The final project of interior design for diploma is the manifestation to students’ understanding on process aspects of interior design that has been studied from the basic to presentation level of design proposal. The chosen product for this project is Cat’s Hotel, The Cat’s Pyjamas at No.5, Jalan Ampang Hilir, 55000 Kuala Lumpur. The purpose of this project is to introduce cat’s care products, deeply, to community and much important is to give service in cat’s care. In running this project, the most important of the cat’s hotel is to make variety of design especially for the cat’s products. Plus, it is also to instill interest of people to cat’s care. The research method for this project is based on observation of cat’s hotel and veterinary through differences of local and international. The advantages that can be seen in this Cat’s Hotel, The Cat’s Pyjamas, is to brighten up the world of cats to community of all level of ages as cats could feel that they are appreciated and one of the family member. In conclusion, the new design cattery that will be run should have the characteristics and customers’ needs besides the suitable concept to be shown. The design hopefully, will give benefits to all, either local or foreigner.